2021
DOI: 10.18632/aging.203029
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis and osteoporosis: a bi-directional Mendelian randomization study

Abstract: Many observation studies have demonstrated a close relationship between rheumatoid arthritis (RA) and osteoporosis (OP). However, the causal genetic correlation between RA and OP remains unclear. In this study, we performed bi-directional Mendelian randomization (MR) analyses to explore causal inference between these two traits. The instrumental variables for RA were selected from a large-scale genome-wide association study (GWAS) (1,523 cases and 461,487 controls). Bone mineral density (BMD) at five different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…59 Furthermore, OP is one of the most severe comorbidities of RA. 60 The KEGG results in this study also illustrated that the RA signaling pathway is the core pharmacological mechanism of RLA against OP and four OP-related genes were regulated by RLA. Further qRT-PCR analysis results of the four genes including opg , rankl , ctsk , and acp5a also demonstrated that the regulation of the RA signaling pathway maybe one of the anti-OP mechanisms of RLA.…”
Section: Discussionsupporting
confidence: 56%
“…59 Furthermore, OP is one of the most severe comorbidities of RA. 60 The KEGG results in this study also illustrated that the RA signaling pathway is the core pharmacological mechanism of RLA against OP and four OP-related genes were regulated by RLA. Further qRT-PCR analysis results of the four genes including opg , rankl , ctsk , and acp5a also demonstrated that the regulation of the RA signaling pathway maybe one of the anti-OP mechanisms of RLA.…”
Section: Discussionsupporting
confidence: 56%
“…e results indicated that the Siwu Decoction formula can effectively improve the BMD of patients with poststroke hemiplegia osteoporosis, improve bone strength, and help patients recover more [21]. 25-OH-VD is the main form of vitamin D in the human body, which is mainly synthesized by human skin after ultraviolet radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between RA and osteoporosis is also inconclusive. The latest two-way Mendelian randomization study shows that there is no obvious causal relationship between RA and osteoporosis (23). However, data from the British Clinical Practice Research Data Link (CPRD) showed that the incidence of OP in RA patients who did not take glucocorticoids was 7.5‰, which was much higher than that in healthy controls.…”
Section: Discussionmentioning
confidence: 99%